2016
DOI: 10.2134/agronj2016.04.0234
|View full text |Cite
|
Sign up to set email alerts
|

Critical Trifoliolate Leaf and Petiole Potassium Concentrations during the Reproductive Stages of Soybean

Abstract: The critical K concentration in soybean [Glycine max (L.) Merr.] has been determined only for leaf tissue at the R2 (full bloom) stage. Our research objective was to develop critical K concentrations in soybean for both leaves and petioles across reproductive stages. Fifteen fully‐expanded, uppermost trifoliolate leaves with petioles plot−1 were collected 7 to 12 times from the V5 to R7 stages in five research trials that evaluated multiple fertilizer‐K rates and/or cultivars from different maturity groups (MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 34 publications
6
39
1
Order By: Relevance
“…The reduction in SY under P deficiency appeared to be closely related to the decreases in the number of pods and seeds per plant as deduced from the greatest CLPC (≈ 2.60 mg P g −1 ) found for these traits. The mean CLKC was also similar between TBM and SY (16.1 mg K g −1 ) and was within the range reported previously (14.6–19.0 mg g −1 ) in soybean ( Parvej et al, ). Factors such as genotype differences, growth conditions, whether the relationship of foliar nutrient status was established with the in‐season biomass or with the TBM and SY at maturity, and the age of plants are likely to influence the critical nutrient concentration.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The reduction in SY under P deficiency appeared to be closely related to the decreases in the number of pods and seeds per plant as deduced from the greatest CLPC (≈ 2.60 mg P g −1 ) found for these traits. The mean CLKC was also similar between TBM and SY (16.1 mg K g −1 ) and was within the range reported previously (14.6–19.0 mg g −1 ) in soybean ( Parvej et al, ). Factors such as genotype differences, growth conditions, whether the relationship of foliar nutrient status was established with the in‐season biomass or with the TBM and SY at maturity, and the age of plants are likely to influence the critical nutrient concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, an early diagnosis of foliar P or K is useful in assisting the correction of deficiency before the nutrient uptake reaches the maximum. The timely diagnosis and remediation of nutrient deficiency also becomes important as the critical nutrient concentration among plant parts, including leaves, varies with the physiological and chronological age as shown in this study and elsewhere ( Bell et al, ; Parvej et al, ). Thus, the period of high demand for mineral nutrients during pod development or seed filling might decrease the foliar P or K concentration due to the remobilization of nutrients in to the developing seeds at later stage.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The relationship between STK and corn grain K in our study ( r 2 = .22) is inconsistent with an Iowa study that reported no relationship between soil test K and corn grain K, with STK values ranging between 75 and 275 mg kg −1 (Mallarino & Higashi, 2009). The relationship between STK and soybean grain K was weak in our study, but is generally consistent with a meta‐analysis drawing on studies conducted in Arkansas, Indiana, Iowa, Missouri, and Canada that found soybean seed K concentrations increased linearly as soil test levels increased up to 179 mg K kg −1 and seed K concentration plateaued at 18.8 g K kg −1 with an r 2 value of .40 (Parvej et al., 2016). To our knowledge, this is the first report of relationships of wheat tissue K concentrations and STK levels in the Midwest.…”
Section: Soil Test K and Tissue K Concentrationssupporting
confidence: 90%